Executive sponsor attributes and megaproject success. (23rd April 2021) - Louw, Willem; Steyn, Herman; Wium, Jan A.; Gevers, Wim
Megaprojects are failing at a rate that affects national economies as well as millions of people. The role of the executive project sponsor is merely one of the decisive factors in the success of these projects, but it is still much neglected in project management literature. This paper investigates attributes required by executive sponsors of megaprojects. The paper reports on the perceptions of 26 executives who played key roles in six recently completed megaprojects. The findings include essential attributes that an executive sponsor should have in order to improve the probability of a megaproject's success. The single most significant attribute is seniority and power.